How Demanding Is Volunteer Work at a Crisis Line? An Assessment of Work- and Organization-Related Demands and the Relation With Distress and Intention to Leave - Renate C. W. J. Willems; Renate C. W. J. Willems; Constance H. C. Drossaert; Harald S. Miedema; Ernst T. Bohlmeijer (Frontiers Media S.A., 2021)
Background: Crisis line services, run by volunteers, offer a listening ear 24/7 to people who cannot or do not want to use professional help. Although previous studies have identified various potential stressors crisis line volunteers face, as yet a comprehensive assessment is lacking with regards to the frequency and perceived stressfulness of work- and organization-related demands, and their relationship with distress and a volunteer's intention to leave.Objective: To identify the frequency and impact of particular stressful situations (demands). In addition, to examine the extent to which these demands are associated with volunteers' demographics, distress and intention to leave the crisis line service.Method: In a cross-sectional study among 543 volunteers of a Dutch crisis line service the participants filled out a questionnaire about their experience of a large number of work- and organization-related demands and their perceived stressfulness. To calculate the impact of demands, the occurrence and stressfulness were multiplied. In addition, work-related distress, intention to leave the crisis line service as well as a number of demographics and work-related characteristics were assessed.Results: Work-related demands with the highest impact on volunteers were calls from people with psychiatric problems and suicidal intentions. "Having no time for a break" was the organization-related demand with the highest impact on volunteers. Eighteen percentage of the volunteers scored moderate or high on distress and 4% had the intention to leave the crisis line service within 1 year. Most work- and organization-related demands were positively associated with volunteers' distress and intention to leave the organization. Being older, being male and spending more hours per week volunteering were significantly, positively correlated with work-related demands. The total explained variance for distress was 16% and for intention to leave 13%.Conclusion: Although most crisis line volunteers experienced low impact from work- and organization-related demands, these demands were significantly related to experienced distress and the intention to leave crisis line service. For volunteers with moderate to high distress it can be useful to implement interventions aimed at increasing personal resources to help them deal with the challenges of the work at the crisis line.